Stride, Soviet! - Beheim, Eric (Flicker Alley, 2011)
In 1925, the city council was up for re-election and commissioned Vertov to make a film for them. Clearly, they expected some kind of propaganda piece; instead they got a provocative, highly innovative work that reflects on one of Vertov's favorite themes, the "humanization of machines" vs. the "mechanization of humanity". Not surprisingly, after suggesting an enormous range of cuts and additions, the authorities refused to show the film. [www.seagullfilms.com]
Keywords: DVD-Video